MENAVIGASI TRANSFORMASI DIGITAL MELALUI EFIKASI DAN KOMPETENSI DIRI PADA WOMENPRENEUR UMKM KADIN BANDUNG - Asmara, Maisa Azizah; Arissaputra, Rivaldi (Program Studi Manajemen Fakultas Ekonomi Universitas Siliwangi, 2024)
Around 70% of MSMEs choose to expand their business online in an effort to avoid bankruptcy. However, between 85% and 95% of these MSMEs fail to adopt digital business models and ultimately face bankruptcy. The main requirement for digital transformation is to have an adaptive and optimistic attitude and work abilities that include aspects of knowledge, skills and work attitudes that are in accordance with expected standards. Data was obtained by distributing questionnaires directly to 21 Womanpreneurs assisted by the Bandung City Chamber of Commerce and Industry in the food and beverage sector. The research uses multiple linear regression analysis methods with the IBM SPSS version 26.0 analysis tool. The research results show that self-efficacy does not have a significant influence on the digital transformation variable, while self-competence has a significant influence. Meanwhile, the coefficient of determination test shows 53.3% of the variation that occurs in the dependent variable. The findings show that self-competence, especially in financial management and innovation, has a greater influence than self-efficacy in the success of digital transformation. Even though Womanpreneurs are confident in running a business, a lack of skills in managing finances can be an obstacle in the digital transformation process.